The Incentive to Invest in Environmental-Friendly Technologies: Dynamics Makes a Difference - Davide Dragone; Luca Lambertini; Arsen Palestini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
The established view on oligopolistic competition with environmental externalities has it that, since firms neglect the external effect, their incentive to invest in R&D for pollution abatement is nil unless they are subject to some form of environmental taxation. We take a dynamic approach to this issue, using a simple differential game to show that the conclusion reached by the static literature is not robust, as the introduction of dynamics shows that firms do invest in R&D for environmental-friendly technologies throughout the game. Moreover, our setup also illustrates the existence of multiple equilibria, only one of which is identified by the corresponding static game.
Keywords: 330